Digitalization of Educational Management to Enhance Accountability and Organizational Transformation in Elementary Schools: A Multisite Study at SDN Pogar II Bangil and SD Nahdlatul Ulama Bangil - Supriatin Supriatin; Ahmad Thohirin; A. Faizin (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Digital transformation has become one of the strategic priorities in educational reform in Indonesia. Digitalization is no longer used solely as a learning medium but has evolved into a key instrument for improving the effectiveness of educational management, accountability, and school governance. This study aims to analyze the implementation of digitalized educational management, identify the factors influencing its successful implementation, and examine its impact on enhancing accountability and organizational transformation in elementary schools. The study employed a qualitative approach using a multisite case study design conducted at SDN Pogar II Bangil and SD Nahdlatul Ulama Bangil, Pasuruan Regency. Data were collected through observations, in-depth interviews, and document analysis involving school principals, teachers, administrative staff, school operators, and other relevant stakeholders. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing, with credibility ensured through source and methodological triangulation. The findings indicate that digitalization has been implemented in various aspects of school management, including academic administration, school information systems, digital attendance, student learning outcome reporting, and communication with parents through digital platforms. The successful implementation of digitalization is influenced by school leadership, the digital competencies of human resources, policy support, and the availability of technological infrastructure. Digitalization has positively contributed to improving transparency, administrative efficiency, data management accuracy, decision-making speed, and organizational culture, leading to more adaptive and accountable school governance. The findings highlight that the digitalization of educational management is not merely the adoption of technology but a comprehensive organizational transformation process that requires strong leadership commitment, human resource readiness, and data-driven governance.